Experimental and Numerical Analysis of Concrete Columns under Axial Load Based on European Design Norms - Florim Grajçevci; Armend Mujaj; Driton Kryeziu; Elfrida Shehu (Civil Engineering Journal, 2024)
This study presents a comparison between numerical and experimental results for reinforced concrete columns subjected to axial compression. Depending on the columns support and their organization within the structure, columns primarily work under either concentric or eccentric compression, respectively, bending in situations where horizontal actions such as wind or/and earthquakes are present in the structure. Different countries have specific design codes, and in this study, the calculation of columns is based on the European design codes, specifically EN 1992-1-1. As a common practice in most cases during research, tests are conducted using computational models, and based on the obtained results through the application of similarity theory, an attempt is made to transition to the actual behavior of structural elements. Therefore, this paper applies a logic of "almost real" testing, where two columns with square cross-sections were produced and tested. The columns had a rectangular base with cross-section dimensions of 20/20 cm and a height (L) of 300 cm, with a concrete strength of fcm,cube=61.80 MPa. They were reinforced with longitudinal reinforcement (4Ø12 mm) and had a tensile strength of ftm=588.10 MPa. Additionally, stirrups of Ø8 mm were placed at every sw=25 cm. Experimental results show a closer alignment with software calculations using SEISMOSOFT with an accuracy of 96%, while results according to EN 1992-1-1, based on simplified methods, show 64% for the Nominal Stiffness Method and 59% for the Curvature Method. Doi: 10.28991/CEJ-2024-010-02-05 Full Text: PDF